(untitled) (Olhar de Professor, 2024)
This article explores the concept of "charter schools" in the United States, which are public institutions managed by private entities, operating under performance contracts. It traces the origin of this proposal in the US, contextualizing it within the school choice movement and providing an overview of the original formulation of charters, as well as a summary of research on their outcomes. In Brazil, there are historical parallels with forms of privatization, such as contracted daycare centers, but recently Brazilian programs inspired by charter schools have emerged, promising efficiency and innovation. The objective of this article is to contribute to the understanding of this phenomenon. To achieve this goal, a bibliographic research was conducted, covering relevant authors in discussions on the topic. It is concluded that the premise that competition, private management, and deregulation are effective strategies to improve the school system is questionable and lacks solid foundation and evidence.